Pengembangan Bahan Ajar Booklet Studi Etnobotani Tumbuhan Obat Masyarakat Ternate - Wahdania Jahun; Juniartin Juniartin; Rosita Tabaika; Astuti Muh. Amin (Al-Nafis: Jurnal Biologi dan Pendidikan Biologi, 2022)
The people of Ternate are part of the local wisdom of the Indonesian people who have traditional knowledge about the use of medicinal plants. This knowledge is passed down from generation to generation. Traditional knowledge about medicinal plants needs to be documented through ethnobotanical research so that it is not lost by the younger generation. The preservation of traditional knowledge is outlined in the form of booklet teaching materials. A booklet is a small book that contains a summary and interesting pictures. Thus, the existence of booklets in learning can not only preserve traditional knowledge, but can also increase students' interest in learning biology. The type of research used is research and development using the ADDIE model (analysis, design, development, implementation, evaluation). The results showed that the percentage of the validity of the booklet teaching materials from the material aspect was 89% with very valid criteria and the validity percentage from the language aspect was 88.9% with very valid criteria From these results, it can be concluded that the teaching materials for the ethnobotany study of medicinal plants of the Ternate community are suitable for use. Keywords: bahan ajar, booklet, ethnobotany, tumbuhan obat